Relationship between the attitude towards homosexuality and religious attitude in physicians of a general hospital - Huarcaya-Victoria, Jeff (2018)
Introduction. It is known that doctors’ attitudes towards gay and lesbian people could influence the type and quality of health care provided. However, there is little information in Peru regarding the attitudes physicians have when facing homosexuality. The objectives of the study were to evaluate the attitudes towards homosexuality and its relationship with some variables in a group of physicians at the “Hospital Nacional Guillermo Almenara Irigoyen”, Lima, Peru. Quantitative, applicative and inductive study approach. Observational and transversal design. Participated 142 physicians aged 24 to 60 years old, 38% female and 62% male. Methods. Attitude towards Homosexuality Scale (EAH-10) and Religious Attitude Scale (EAR), sociodemographic variables were also gathered. Results. The mean EAH-10 score was 23, 32. Forty-six (32,4%) physicians showed intolerant attitudes towards homosexuality, being these higher in male (p=0,005), catholic and protestant/evangelical (p=0,007). A positive linear correlation was found in men between religious attitude and homophobic attitudes (r=0,343, p=0,001), and between the age and homophobic attitudes (r=0,204, p=0,015). The number of close homosexual people known showed a negative correlation with the homophobic attitudes (r=-0,218, p=0,001). Multivariate linear regression analysis showed that male, marital status (divorced / cohabitant) and EAR are associated with EAH-10. Conclusions. In the analyzed population of physicians, a significant positive relation was found between religious attitude and homophobic attitudes, and between age and homophobic attitudes. Also, a significant negative relation was found between the number of close homosexual people known and homophobic attitudes.